2022
DOI: 10.1111/bjh.18249
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residual disease and imaging‐guided consolidation strategies in newly diagnosed and relapsed refractory multiple myeloma

Abstract: Measurement of minimal residual disease (MRD) by next-generation flow cytometry (NGF) is an important tool to define deep responses in multiple myeloma (MM).However, little is known about the value of combining NGF with functional imaging and its role for MRD-based consolidation strategies in clinical routine. In the present study, we report our experience investigating these issues with 102 patients with newly diagnosed (n = 57) and relapsed/refractory MM (n = 45). Imaging was performed using either positron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…Beyond the sensitivity of next-generation methods that measure MRD inside the BM, the role of PET/CT to refine depth of response appears to be particularly valuable in RRMM due to the increased incidence of extramedullary disease ( 16 ). Accordingly, the presence of extramedullary disease after infusion with ide-cel was associated with inferior PFS in patients achieving undetectable MRD.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the sensitivity of next-generation methods that measure MRD inside the BM, the role of PET/CT to refine depth of response appears to be particularly valuable in RRMM due to the increased incidence of extramedullary disease ( 16 ). Accordingly, the presence of extramedullary disease after infusion with ide-cel was associated with inferior PFS in patients achieving undetectable MRD.…”
Section: Discussionmentioning
confidence: 99%
“…Enabling individual, detailed monitoring of all local processes is urgently needed in MM, given the recent insights about the spatial heterogeneity and the spatiotemporal evolution of the disease, [18][19][20] as well as the recent evidence that functional whole-body imaging delivers complementary information to BM biopsies in minimal residual disease assessment of MM patients. [65][66][67]…”
Section: Discussionmentioning
confidence: 99%
“…Given the established link between local radiomics signatures and local tumor tissue characteristics, such machine learning models have the potential to inform on local tumor tissue characteristics multifocally across the complete BM, and thereby capture the spatially heterogeneous tumor manifestations and complex biological patterns observed in MM. Enabling individual, detailed monitoring of all local processes is urgently needed in MM, given the recent insights about the spatial heterogeneity and the spatiotemporal evolution of the disease, 18–20 as well as the recent evidence that functional whole-body imaging delivers complementary information to BM biopsies in minimal residual disease assessment of MM patients 65–67 …”
Section: Discussionmentioning
confidence: 99%
“…Rasche et al showed, in a large cohort, that 12% of patients found to be MRDnegative after induction therapy still had positive FLs on 18 F-FDG PET/CT analysis (110). Recently, a study by B€ ockle et al included 102 patients with newly diagnosed MM (n 5 57) and relapsed or refractory MM (n 5 45), who achieved a good partial response, a complete response, or a stringent complete response by International Myeloma Working Group 2016 criteria (111). Functional imaging ( 18 F-FDG PET/CT or diffusion-weighted MRI) was performed independently of bone marrow MRD results.…”
Section: Potential Of 18 F-fdg Pet/ct For Therapy Assessment and Mrd ...mentioning
confidence: 99%